The Relevance of Ibn Khaldun Concept of 'Ashabiyah to the Advancement of Science During the Mamluk Dynasty: Relevansi Konsep ‘Ashabiyah Ibn Khaldun dalam Perkembangan Ilmu Pengetahuan Pada Masa Dinasti Mamluk - Pangaribuan, Nuraini (The Department of Islamic History and Culture in cooperation with the Center for Islamic History and Culture in Aceh and Malay World Studies (PUSAKA), Universitas Islam Negeri Ar-Raniry Banda Aceh, Aceh, Indonesia, 2026)
This study aims to explore the relevance of Ibn Khaldun's concept of 'Ashabiyah to the solidarity of slaves (mamalik) in supporting the development of science during the Mamluk Dynasty. This study is a library research using qualitative methods with a historical-analytical approach. The results of the study show that the concept of 'ashabiyah popularized by Ibn Khaldun is a socio-political concept that focuses on the dynamics of group power and social solidarity in building and maintaining civilization. This is relevant to the establishment of the Mamluk Dynasty, which was followed by the advancement of science during the Mamluk Dynasty. This period of progress was realized by the slaves (mamalik), who were known to have a very strong sense of social solidarity and high loyalty to their leaders and tribes, enabling them to achieve their main goal, namely the development of science in various fields, which reached its peak during that period. The power of social solidarity during the Mamluk Dynasty is relevant to Ibn Khaldun's concept of 'ashabiyah, which encourages the creation of an environment conducive to the advancement of science